A quadratic demand EOQ model for deteriorating items with time dependent shortage. (9th September 2021) - Sindhuja, S.; Arathi, P.; Mohan, Varun
In an inventory model, optimising the time and cost is a challenging task. This article focuses on an economic order quantity model (EOQ model) with a quadratic demand and constant deterioration of items. The aim of the paper is to provide a methodology to minimise the total cost in an EOQ model. This is achieved by increasing the deteriorating items, under the normal market conditions and considering the demand as a quadratic demand. Shortage in cost is similarly considered. A numerical example is discussed and compared with an existing model to illustrate the behaviour of the quadratic demand rate. There is a considerable reduction in total cost in the proposed model when compared with the existing model. Sensitivity analysis concerning the changes in parameters is carried out through the graphical representations. Complex algebraic equations are solved using MATLAB R2013a.